Effect of cisplatin in Mytilus galloprovincialis and of cyclophosphamide, tamoxifen and cisplatin on Ca2+ATPase - Morais, Matilde (2016)
Relatório de Estágio de Licenciatura, Biologia Marinha, Faculdade de Ciências e Tecnologias da Universidade do Algarve, 2015